"Fazer o bem sem olhar a quem": o trabalho voluntário à luz da religiosidade, sentido de vida e valores humanos - Silva, Anne Emanuelle Cipriano da (2017)
According to Viktor Frankl´s theory men can live and die for their values and ideals, considering the search for a meaning in life as the primary motivation of human beings. Also, in a certain way volunteer work is historically associated to religious individuals. Therefore the current work aimed to verify which evaluative sub-functions are related to the presence of meaning and also to find out the relationship between religious attitudes and meaning in life in the experience of volunteers belonging to a Non-Governmental Organization (NGO) that works with health related issues in the city of João Pessoa. The sample group was formed by 69 volunteers of both genders in a mean age of 57 (sd = 10.77) varying between 28 and 77 years old. The majority were women (82.6 %). The participants answered to the following instruments: Meaning in Life Questionnaire (MLQ), Religiousness / Spirituality Attitude Scale (RAS-20), Basic Value Survey (BVS), Socio-demographic Survey. During the research a field diary was also used by the researcher. The results suggested positive correlations between the Presence of Meaning and the evaluative sub-functions Existential (r = 0.38, p < 0.5) and Normative (r = 0.29, p < 0.5). They also suggested a negative correlation between the Presence of Meaning and the evaluative sub-function Experimentation (r = -0.26, p < 0.05). Regarding the Religious Attitude, the Presence of Meaning was directly associated to the Religious Knowledge (r = 0.27, p < 0.05) and to the Religious Behavior (r = 0.27, p < 0.05), being inversely associated to the Religious Embodiment (r = -0.27, p < 0.05). The Search for Meaning associated itself directly with the Experimentation (r = 0,29, p < 0,05). The results were discussed according to the Functional Theory of Human Values and to Logotherapy and Existential Analysis. It was concluded that in the searched volunteers meaning in life is positively related to religious attitude and evaluative sub-functions.